2016
DOI: 10.1007/978-3-319-46843-3_4
|View full text |Cite
|
Sign up to set email alerts
|

Anomaly Detection in Elderly Daily Behavior in Ambient Sensing Environments

Abstract: Abstract. Current ubiquitous computing applications for smart homes aim to enhance people's daily living respecting age span. Among the target groups of people, elderly are a population eager for "choices for living arrangements", which would allow them to continue living in their homes but at the same time provide the health care they need. Given the growing elderly population, there is a need for statistical models able to capture the recurring patterns of daily activity life and reason based on this informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 28 publications
(34 reference statements)
0
47
0
Order By: Relevance
“…Aran et al [106] take a similar approach to the one proposed by Lotfi et al Like Lotfi's work, Aran infers the current location of a smart home resident and uses k means clustering to group similar data points based on time of day, location, and time spent in the location. The clustering algorithm provides a convenient basis for determining outliers as data points that do not fit well in any of the existing clusters.…”
Section: Detecting and Assessing Threatsmentioning
confidence: 99%
“…Aran et al [106] take a similar approach to the one proposed by Lotfi et al Like Lotfi's work, Aran infers the current location of a smart home resident and uses k means clustering to group similar data points based on time of day, location, and time spent in the location. The clustering algorithm provides a convenient basis for determining outliers as data points that do not fit well in any of the existing clusters.…”
Section: Detecting and Assessing Threatsmentioning
confidence: 99%
“…Zhao et al used a novel computer-vision-based system consisting of inexpensive programmable depth sensors, wearable devices, and smart phones to ensure worker safety in the workplace without violating their privacy [14]. Aran et al proposed an indicator of predictability based on the cross-entropy measure for the detection of anomalies in elderly daily behavior [15]. Alcalá et al used a novel approach to identify appliance activities from smart meter data and extract the pattern of usage, which is used to monitor the health of the household's occupant [16].…”
Section: Related Workmentioning
confidence: 99%
“…However, this also leads to privacy issues as well as creates high dependency to people (i.e., users have to carry these devices all the time). Another method includes using ambient sensors [11,12], e.g., infrared or ultrasonic sensors, but the outcomes of these can be highly unreliable due to sensor quality. A recent study [1] showed that activity detection of a single person can be achieved with ambient sensors.…”
Section: Introductionmentioning
confidence: 99%